Approach for a breastshot waterwheel numerical simulation methodology using six degrees of freedom - Warjito; Aji Putro Prakoso; Dendy Adanta; Budiarso; Ridho Irwansyah (Energy Reports, 2020)
Breastshot waterwheels are suitable for low head conditions in power plants because they have more stable efficiency than other types of turbines do. In some cases, computational fluid dynamics (CFD) methods have been utilised for the performance prediction, geometry optimisation or determination of physical phenomena of a breastshot waterwheel because such approaches offer efficiency in terms of energy, time and cost. However, the dynamic approach of the CFD method is different from that in real conditions. For improving the accuracy of CFD simulation results, a feature of 6-degrees of freedom (6-DoF) can be an alternative. This study presented the CFD method using the 6-DoF feature in a breastshot waterwheel. Based on the grid convergence index (GCI) and timestep convergence index (TCI) concepts, 123~000 elements of mesh and a timestep size of 0.002 s were used in this simulation because these parameters fulfilled the GCI and TCI maximum thresholds. The preload values were varied in the simulation, with levels of 75 N·m, 150 N·m, 225 N·m and 300 N·m. Based on the results, the rotation and torque produced by the wheel resulted in a transient period until they naturally became steady. (The rotation and torque were stable). This is the real-world phenomenon of the energy conversion process in a breastshot waterwheel, which cannot be calculated by other features in the CFD method. Thus, the 6-DoF feature can be a suitable option for breastshot waterwheel turbine simulations for performance prediction, geometry optimisation or studying physical phenomena.
Keywords: 330; Breastshot; Computational fluid dynamics method; Six-degrees of freedom; Waterwheel